A closed-loop supply chain model with rework, waste disposal, and carbon emissions. (2020) - Jauhari, Wakhid Ahmad; Adam, Niimas Ayu Frensilia Putri; Rosyidi, Cucuk Nur; Pujawan, I Nyoman; Shah, Nita H.
Highlights: We proposed a closed-loop supply chain consisting of three parties under five coordination scenarios. The market demand is linearly dependent on the green technology level, the retailer selling price, and the quality of the product. A carbon cap-and-trade policy and green technology investment are applied in the model. Remanufacturing and refurbishing processes are used to recover the used products. A collector conducts a collection effort investment to increase the collection rate of used products. Abstract: This paper develops a closed-loop supply chain model consisting of a single manufacturer, single retailer, and single collector under various coordination scenarios. New products produced from the manufacturing and remanufacturing processes will be sold to the market at the same price. Used products collected by the collector are sorted so that products categorized as recoverable will be sold to the manufacturer. There are two recovery processes considered in this paper, namely remanufacturing and refurbishing. Used products below the minimum acceptable quality level of the manufacturer will be categorized as waste and will be disposed of. We assume that the manufacturing process is imperfect as it produces reworkable defective products. A carbon cap-and-trade policy and investment in green technologies are applied in order to restrict the carbon emissions generated by the production stage of the system. The demand at the market place depends on the green technology level, the quality of the product, and the selling price. The proposed model is constructed under five different scenarios – centralized, decentralized, and three Stackelberg games led, respectively, by the manufacturer, retailer, and collector. A numerical example is provided to illustrate and compare the proposed model under each scenario and investigate the sensitivity of some of the model parameters on the optimal solutions. The results show that the centralized scenario performs better in maximizing the total profit compared to the decentralized one. However, the retailer-led Stackelberg model tends to give more equitable profit to all players when the selling price is set at the lower level as this will attract more demand.